Old Names, New Peoples: Listing Ethnonyms in Late Antiquity - Liccardo, Salvatore, author.
1 online resource (346 pages)
Keywords: No people is nameless, and lists of words are as old as writing systems. And yet, both subjects can appear unpromising to historians. This volume shows the contrary by examining the various meanings and functions of ethnonyms in Late Antiquity: added to catalogues of provinces, they reflect the political messages and the regulating power of the imperial bureaucracy; included in schoolbooks, they mirror educational practices and reveal the geographical and ethnic landscapes taught at school; placed on a map, they help make sense of the world in times of transition.